Journal of Plant Biology - Kim, Woo Taek.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Journal of Plant Biology, an official publication of the Botanical Society of Korea, is an international journal devoted to basic researches in biochemistry, cellular biology, development, ecology, genetics, molecular biology, physiology, and systematics of plants. The Journal publishes the following categories of paper: Original articles -- For publication in Journal of Plant Biology the manuscript must provide a significant new contribution to our understanding of plants. All areas of plant biology are welcome. No limit on the length, but a concise presentation is encouraged. Reviews -- Invited by the EiC. Brief Communications -- Concise but independent report representing significant contribution to plant science. The Botanical Society of Korea was founded on November 30, 1957 to promote studies, disseminate and exchange information on the field of plant biology. The first issue of The Korean Journal of Botany, the official publication of the society, was published on April 1, 1958. It was published twice a year, but quarterly from 5th volume in 1962. In 1994, it was renamed to Journal of Plant Biology and published in English since 1996. The journal entered its 50th year of publication in 2007.
Keywords: Plant ecology; Plant science; Botany; Plant systematics; Plant taxonomy; Plant breeding; Plant Sciences; Plant Breeding/Biotechnology.; Plant Genetics and Genomics; Plant Systematics/Taxonomy/Biogeography.; Plant Ecology